Potential impacts of typhoon tracks on storm surge and typhoon wave in the Beibu Gulf: a case study of Super Typhoon Rammasun - Wu, Zhiyuan; Zhang, Shuai; Wei, Wen; Gao, Kai; Chen, Jie; Jiang, Changbo; Deng, Bin (Frontiers in Marine Science, 2025)
Frequent typhoons in the Beibu Gulf pose a significant threat to marine and coastal infrastructure. To address this issue, we applied a fully integrated tide-surge-wave model using the Holland typhoon model and Delft3D-FLOW-WAVE. The model simulates storm surge and typhoon waves generated by Super Typhoon Rammasun (2014). We generated five idealized typhoon tracks by systematically shifting Rammasun’s track to evaluate their potential impacts on storm surge and waves. The results indicate that nearshore storm surges in the Beibu Gulf exhibit a distinct rise-then-fall pattern, with the maximum surge occurring on the right-hand side of the typhoon track. Surge magnitude diminishes as the track shifts eastward. Significant wave heights undergo marked spatial redistribution upon the typhoon’s entry into the Gulf, transitioning from left- to right-biased asymmetry during passage. Coastal ports in the Beibu Gulf and the eastern Leizhou Peninsula experience pronounced positive surges, while the highest surge and wave intensities occur along northeastern Hainan Island and both sides of the Qiongzhou Strait. Although based on idealized tracks, this study offers critical insights for optimizing coastal disaster mitigation against extreme typhoons in the region.